Evaluating the safety and feasibility of remote ischemic conditioning for slowing cognitive decline in mild Alzheimer’s dementia - Huang, Xin; Ji, Qiling; Tong, Tanna; Cai, Lipeng; Elmadhoun, Omar; Zeng, Yanfang; Geng, Xiaokun; Ding, Yuchuan (Frontiers in Neurology, 2025)
ObjectiveAlzheimer’s disease (AD) is characterized by complex pathological mechanisms involving neuroinflammation, oxidative stress, and vascular dysfunction. Remote Ischemic Conditioning (RIC) has shown potential in addressing these pathways by improving cerebral blood flow, reducing oxidative stress, and modulating inflammatory responses. This protocol focuses on evaluating the safety, feasibility, and preliminary efficacy of RIC as a multi-target intervention for delaying cognitive decline in patients with mild Alzheimer’s dementia, aiming to improve cognitive outcomes and overall quality of life.Methods and expected resultsThis study is a randomized, controlled, single-center, prospective clinical trial designed to evaluate the safety, feasibility, and preliminary efficacy of RIC in patients with mild Alzheimer’s dementia. Eligible participants will be recruited and randomly assigned to either the RIC group or a control group receiving sham RIC, with 20 patients in each group. Participants will receive either RIC or sham RIC once daily over a 3-month period. Outcome measures will assess cognitive function, psychological well-being, and inflammatory and neurodegenerative biomarkers. Psychiatric adverse events will be monitored throughout the treatment using the Hamilton Anxiety Rating Scale (HAMA) and the Hamilton Depression Rating Scale (HAMD-17). Cognitive function and daily living abilities will be evaluated at baseline, 3 months, 6 months, and 12 months post-treatment using the Mini-Mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA), Clinical Dementia Rating (CDR), and the Activities of Daily Living (ADL) scales. In addition, blood samples will be collected at each time point to measure plasma biomarkers of β-amyloid species and serum inflammatory cytokines to assess potential changes in cognitive decline, disease progression, and inflammation. The primary endpoint is safety, with the expectation that RIC will not increase psychiatric adverse events as reflected in HAMA and HAMD-17 scores. Primary efficacy endpoints include improvements in MMSE, MoCA, CDR, and ADL scores, indicating potential cognitive benefits and enhanced daily functioning. Secondary endpoints will analyze biomarkers to evaluate disease progression and inflammation levels before and after treatment.ConclusionThis trial aims to determine the safety, feasibility, and potential effectiveness of RIC as a multi-target intervention for mild Alzheimer’s dementia by integrating cognitive and neuropsychological assessments with biological markers, providing a foundation for future studies.